From catastrophe to complexity: a novel model of integrative central neural regulation of effort and fatigue during exercise in humans - Noakes, T. D.; St. Clair Gibson, A.; Lambert, E. V. (British Journal of Sports Medicine, 2004)
It is a popular belief that exercise performance is limited by metabolic changes in the exercising muscles, so called peripheral fatigue. Exercise terminates when there is a catastrophic failure of homoeostasis in the exercising muscles. A revolutionary theory is presented that proposes that exercise performance is regulated by the central nervous system specifically to ensure that catastrophic physiological failure does not occur during normal exercise in humans.